Quartz-helium method to estimate fluid flow in thick aquitards, Gunnedah Basin, Australia - Smith, Stanley D.; Mathouchanh, Emeline; Mallants, Dirk (Groundwater, 2019)
The hydraulic integrity of aquitards is generally assumed and relies on a few core-scale permeability measurements, drill-stem tests, or textbook values. This approach is because hydraulic data across the full aquitard thickness is generally lacking. Proper assessment of aquitard integrity should be studied at the formation (spanning its entire thickness at a single point) or regional (formation properties at multiple locations throughout the basin) scale. One formation-scale approach uses environmental tracers and advection-dispersion modeling to constrain fluid flow rates. This study demonstrates the use of helium concentrations in quartz as a method of constraining the rate of fluid flow in a 520-m thick aquitard in the Gunnedah Basin, NSW, Australia. Quartz was separated from existing core samples in the Watermark and Porcupine Formations at depths from 750 to 1200 m. The helium was released from these samples by heating and select samples were impregnated with helium to determine the rate of helium diffusion through the quartz. One-dimensional advection-dispersion modeling of the helium profile accounting for diffusive helium exchange between quartz and pore water revealed, that (1) vertical fluid velocity has been on the order of 0.02 mm/year or less for tens to thousands of years, (2) helium is in equilibrium between quartz and pore water, and (3) the helium profile is transient indicating that helium concentrations in the underlying Maules Creek Formation has varied over geological time. Further modeling identified aquitard conditions (thickness and temperature) for which equilibrium exists, a precondition for deriving formation-scale permeability.